1981
DOI: 10.1093/nar/9.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of transcription by RNA polymerase II in permeable, SV40-infected or noninfected, CV1 cells; evidence for multiple promoters of SV40 late transcription

Abstract: CV1 cells were made permeable by treatment with lysolecithin and incubated in a transcription mixture containing ribonucleoside triphosphates including ATP or GTP 32P-labeled either in the alpha or beta position. 5'-terminal cap structures (7mGpgamma pbeta palpha X) on newly synthesized RNA were analyzed by digestion with nuclease P1 or with ribonuclease T2/bacterial alkaline phosphatase. Cap structures obtained after labeling with alpha-32P-GTP show that the 32P is found only adjacent to the 7mG residue (i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 55 publications
0
34
1
Order By: Relevance
“…To explore this possibility, we performed in vivo footprinting of the proximal promoter of KDR/flk-1 by LM-PCR in cells treated with DNase I after permeabilization with lysolecithin. This permeabilization technique does not inhibit transcription initiation and should therefore maintain a faithful promoter architecture for probing with DNase I (27). Compared with in vitro DNase I-treated purified genomic DNA, HUVEC genomic DNA treated in vivo was strongly protected over the four Sp1 sites defined as being important in our previous in vitro experiments (Fig.…”
Section: In Vivo Analysis Of the Kdr/flk-1 Promoter By Lm-pcr-we Hypomentioning
confidence: 83%
“…To explore this possibility, we performed in vivo footprinting of the proximal promoter of KDR/flk-1 by LM-PCR in cells treated with DNase I after permeabilization with lysolecithin. This permeabilization technique does not inhibit transcription initiation and should therefore maintain a faithful promoter architecture for probing with DNase I (27). Compared with in vitro DNase I-treated purified genomic DNA, HUVEC genomic DNA treated in vivo was strongly protected over the four Sp1 sites defined as being important in our previous in vitro experiments (Fig.…”
Section: In Vivo Analysis Of the Kdr/flk-1 Promoter By Lm-pcr-we Hypomentioning
confidence: 83%
“…Notably, this approach is different from the two previous ones as it leaves the rest of the RNA body completely unlabeled. It is also possible to obtain RNA selectively radiolabeled at the b-phosphate of the cap by adding an appropriate [b-32 P] NTP to the transcription reaction [42]. However, to our knowledge, this approach is rarely used, likely owing to a lack of commercial availability of [b-32 P] NTPs.…”
Section: Incorporation Of 32 P Into Rna Capsmentioning
confidence: 99%
“…The identity of the cap structures can be confirmed by isolation and further digestion by a pyrophosphatase with broad specificity, such as tobacco acid pyrophosphatase (TAP), which cleaves both triphosphate bonds. This approach has been used to identify 5 0 ends of eukaryotic and viral mRNAs, snRNAs, and snoRNAs [42][43][44][45], as well as to verify the P-labeled RNAs using in vitro transcription followed by enzymatic capping. Depending on the template sequence and 'hot' NTP used in the transcription reaction, RNA can be labeled at the a position within the cap triphosphate bridge (1) or at the first phosphodiester bond of transcribed RNA (2).…”
Section: Incorporation Of 32 P Into Rna Capsmentioning
confidence: 99%
“…However, there is some indirect evidence that capping may happen elsewhere than at the initial nucleotide in an RNA chain (Schibler & Perry, 1976;Spencer et al, 1978). On the other hand, recent studies using permeabilized cells or isolated nuclei (Contreras & Fiers, 1981;Gidoni et al, 1981) and in vitro transcription systems (Handa et al, 1981) have shown that initiation of transcription can take place at capping sites on the DNA of the related simian virus 40 (SV40). The present study was undertaken to provide independent evidence for the in vivo location of transcriptional initiation sites.…”
Section: Introductionmentioning
confidence: 99%